ASSOCIATION OF POLYMORPHISM IN BIOTRANSFORMATION SYSTEM GENES CYP1A1 AND GST WITH RISK OF RELAPSE IN CHILDHOOD ACUTE LEUKEMIA - O.A. Gra (Union of pediatricians of Russia, 2007)
Presence of polymorphism in genes coding biotransformation system may play an important role in formation of primary childhood acute leukemia, and affects the incidence and features of relapse. We developed a biological microchip which allows to analyze 14 mutations in eight genes of biotransfor mation system: cyp1a1, cyp2d6, gstt1, gstm1, nat2, mthfr, cyp2c9 and cyp2c19. This biochip has been used to study DNA samples from 332 children with diagnosis of acute lymphoblastic leukemia (all) and 71 children with diagnosis of acute myeloblastic leukemia (AML). it was obtained that variant genotype cyp1a1 *1/*2а more often occur in children with relapse of disease than in children with primary diagnosed leukemia (or = 2,11, p = 0,0291). Also it has been shown, that «null» gstt1 genotype is less frequent in children with relapse of disease than in children with primary diagnosed leukemia (or = 0,55, p = 0,0265). Upon sex stratification, boys with relapse of all demonstrated an increased occurrence of the cyp1a1 genotype *1/*2а in combination with the gstt1 «nonnull» genotype relative to patients with primarily diagnosed all (or = 3,09, p = 0,0254). In addition, girls with relapse of acute leukemia displayed a 2,4_fold lower frequency of the «null» gstm1 genotype as compared with the girls group with primary leukemia (or = 0,41, p = 0,0175). Thus, it was shown that studied genotypes cyp1a1 and GST might be prognostic risk factors of relapse in childhood acute leukemia.Key words: acute leukemia, drug resistance, cytochrome p 450, glutathione-s-transferases, polymorphism, oligonucleotide biochips.